Pathogenesis of pulmonary hypertension caused by left heart disease - Xiao, Mingzhu; Lai, Disheng; Yu, Yumin; Wu, Qingqing; Zhang, Caojin (Frontiers in Cardiovascular Medicine, 2023)
Pulmonary hypertension has high disability and mortality rates. Among them, pulmonary hypertension caused by left heart disease (PH-LHD) is the most common type. According to the 2022 ESC/ERS Guidelines for the diagnosis and treatment of pulmonary hypertension, PH-LHD is classified as group 2 pulmonary hypertension. PH-LHD belongs to postcapillary pulmonary hypertension, which is distinguished from other types of pulmonary hypertension because of its elevated pulmonary artery wedge pressure. PH-LHD includes PH due to systolic or diastolic left ventricular dysfunction, mitral or aortic valve disease and congenital left heart disease. The primary strategy in managing PH-LHD is optimizing treatment of the underlying cardiac disease. Recent clinical studies have found that mechanical unloading of left ventricle by an implantable non-pulsatile left ventricular assist device with continuous flow properties can reverse pulmonary hypertension in patients with heart failure. However,the specific therapies for PH in LHD have not yet been identified. Treatments that specifically target PH in LHD could slow its progression and potentially improve disease severity, leading to far better clinical outcomes. Therefore, exploring the current research on the pathogenesis of PH-LHD is important. This paper summarizes and classifies the sresearch articles on the pathogenesis of PH-LHD to provide references for the mechanism research and clinical treatment of PH-LHD, particularly molecular targeted therapy.